THE SIGNIFICANCE OF HISTORICAL WORKS CONTAINING PATRIOTIC FEELINGS IN CHILDREN’S THEATERS (American Journal of Interdisciplinary Research and Development, 2022)
In this article, children’s theater plays an important role in educating the young generation and it is recognized as an important factor in expanding their worldview, developing their consciousness and thinking. Fiction, historical works embody children’s feelings of patriotism and love for the country is highlighted in our article.